266 The Effect of the COVID-19 Pandemic on Emergency Theatre Mortality, Time to Intervention and Length of Stay in the First Phase of National Lockdown at a District General Hospital. (12th October 2021) - Luo, W; Limb, R; Aslam, A; Kattimani, R; Karthikappallil, D; Paramasivan, A; Waseem, M
Abstract: Aim: This study aimed to investigate the patient population requiring emergency surgery during the first phase of lockdown due to COVID-19 in the United Kingdom and compare it to the equivalent population in the same calendar period for 2019. Thus, we aimed to evaluate the impact of the pandemic on emergency operations. Method: We retrospectively reviewed patients undergoing surgery in emergency theatres at our district general hospital between March 23 rd and May 11 th in 2019 and 2020. Data collected included demographics (age/gender), National Confidential Enquiry into Patient Outcome and Death (NCEPOD) category and operation. The primary outcome was 90-day post-operative mortality; secondary outcomes included time to intervention and length of inpatient stay. Results: 132 (2020) versus 141 (2019) patients were included with no significant difference in age (p = 0.676) nor sex (p = 0.230). There was no difference in overall 90-day postoperative mortality (p = 0.196). Notably, time to intervention was faster for NCEPOD code 3 patients in 2020 than in 2019 (p = 0.027). Time to intervention in 2020 was longer for those dying within 90 days post-operatively compared to survivors (p = 0.02). There was no difference in length of stay between the years, both overall and when conducting subgroup analyses by NCEPOD category or procedures (fractured neck of femur (p = 0.776), laparoscopies (p = 0.866), laparotomies (p = 0.252)), except for upper limb trauma (p = 0.007). Conclusions: Patients were appropriately prioritised with no overall change in mortality or length of stay. A national validation audit assessing outcomes of emergency operations during these challenging times would further elucidate risks posed to surgical patients requiring urgent care.